THE INFLUENCE OF COMPANY SIZE, PROFITABILITY, AND OWNERSHIP STRUCTURE ON COMPANY VALUE (CASE STUDY ON PROPERTY AND REAL ESTATE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE. 2020-2023) - Wany, Eva; Prayitno, Budi; Abidin, Khoirul (International Journal of Accounting Innovation, 2025)
Objective: This study aims to examine the impact of company size, profitability, and institutional ownership on the value of property and real estate companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. Methods: Utilizing a quantitative approach, data were analyzed using SPSS, specifically employing multiple linear regression to assess the relationships between the independent variables (company size, profitability, and institutional ownership) and the dependent variable (company value). The sample was selected through purposive sampling of IDX-listed property and real estate companies within the study period. Results: Findings indicate that while company size does not significantly influence company value, profitability and institutional ownership positively impact company value in the property and real estate sector. Novelty: This research contributes to the field by highlighting the role of institutional ownership in enhancing company value within the Indonesian property and real estate market, providing sector-specific insights that may assist stakeholders in optimizing firm strategies and governance.